Forever young : the teen-aging of modern culture - Danesi, Marcel, 1946- (University of Toronto Press, 2003)
"The excessive worship of adolescence and its social empowerment by adult institutions is the deeply rooted cause of a serious cultural malaise. So argues semiotician Marcel Danesi in Forever Young, an unforgiving and controversial look at modern culture's incessant drive to create a 'teen-aging' of adult life." "Written for the general reader and based on five years of interviews with over two hundred adolescents and their parents, Danesi's book begins by asserting that one of the early causes of this crystallization of adolescence as an age category can be traced back to theories of psychology at the turn of the twentieth century. Since then, the psychological view of adolescence as a stressful period of adjustment has become a self-fulfilling prophecy. This, in tandem with the devaluation of the family by the media and society at large, had led to a maturity gap - a fissure in family dynamics that is eagerly and ably exploited by the mass media." "Unlike many academic digressions into the malaise of modern culture, Forever Young provides concrete answers on how the 'forever young syndrome' can be addressed. One solution is to dispel the myth that experts and professionals are the people best equipped to give advice on raising children. The second is to recognize the value of family, in all its different combinations, as the primary institution of child rearing. The third is to challenge the pervasive notion that teen culture is a sophisticated endeavour - that, for example, pop music can claim to have produced some of the best musical art in the world, surpassing Mozart or Bach."